Corak Pemikiran Hasbi Ash-Shiddieqy terhadap Fiqh Indonesia (Antara Moderasi dan Purifikasi) - Khairunnas Jamal; Derhana Bulan Dalimunthe (STAIN Bengkalis, 2020)
Hasbi was a very noted exegetes environmental conditions of communities, the form is kontekstualisasi the verses of the Qur'an. The thought of giving new color Hasbi in the scientific study of fiqh Indonesia. A variety of shades of science that it had become a powerful weapon in the face of Indonesia Society condition. It is because society still considers Indonesia an Islamic academic as foreign. This article examines the pattern of thought Hasbi in misinterpretation glance between purifikatif and modernisation. This of course can not be separated from the background in the face by Hasbi. The results of this study demonstrate that consistent Hasbi as modernist because in determining any legal issue, Hasbi not only use but also aqli naqli propositions.